Fixed Point Theorems for Multiplicative Cyclic \((α,β)\)-Convex Contraction of Type-2 in Dislocated Quasi \(b\)-Multiplicative Metric Space and Its Applications - Dharsini, A. Mary Priya; Lavino, P. Joselin (Communications in Mathematics and Applications, 2024)
The dislocated quasi \(b\)-multiplicative metric space is introduced as an extension of dislocated quasi \(b\)-metric space, which is demonstrated some well-known fixed point theorems and shows fixed point results for a contraction of rational type. Specifically, we generalize the convex contraction to encompass the dislocated quasi \(b\)-multiplicative setting. The results of this study not only contribute to the theoretical foundations of fixed point theory but also offers a new perspective on the applicability of dislocated quasi \(b\)-multiplicative metric spaces.